Structural Analysis of Injection Control System and Methods to Correct Air Fuel Ratio - Trần Thanh Thưởng (Journal of Technical Education Science, 2006)
This paper introduces methods to correct air-fuel ratio of gasoline injected engine based on the operation of electronic fuel injection control system and structural analysis of electronic control unit.